Do ambulance crews triage trauma patients?. Issue 3 (September 1991) - Rouse, A
Abstract : OBJECTIVE. To determine whether ambulance crew triage trauma patients appropriately. DESIGN. A retrospective descriptive study. SETTINGS. Cornwall County Ambulance Service. VARIABLES STUDIED. On-scene times, injury severity, establishment of intravenous infusion and time from scene to A&E department. SUBJECTS. Patients with compound fracture of the lower limb taken to Truro Accident and Emergency department. OUTCOME MEASURES. Ambulance service on-scene times and mission times. RESULTS. Ambulance crew do not appear to be triaging patients appropriately. Excessive time is being spent on pre-hospital stabilization. Delivery of patients to a casualty department is delayed. CONCLUSION. At present the activities of paramedics are poorly supervised, and pre-hospital management by paramedics may be jeopardizing patient care.